Construction land transition in Qinghai-Tibet Plateau and its eco-environmental effects during 2000-2020 - ZHANG Zining, LUO Junqiang, ZHANG Peilei, RONG Han, LIU Haiyang, AN Shuang, CHANG Genying (Ziyuan Kexue)
[Objective] Land resources are critical factors supporting the rapid development of society and economy. However, their transition during urbanization processes poses significant ecological and environmental challenges. The Qinghai-Tibet Plateau, as a typical ecologically fragile and sensitive region, requires balanced strategies for rational development and ecological conservation. In this context, the explicit morphological changes of construction land drive the transition of regional land use, and the ecological and environmental effects generated thereby deserve more attention. [Methods] Based on land use and remote sensing image data from 2000 to 2020, this study analyzed construction land transitions on the Qinghai-Tibet Plateau. By developing an improved remote sensing ecological index (IRSEI), the study further examined the ecological effects of land-use type transitions and their regional differences in contributions to local ecological environments. The findings aim to provide a reference for the coordinated development of resources and environment on the Qinghai-Tibet Plateau. [Results] (1) Construction land on the Qinghai-Tibet Plateau had predominantly increased, with only a small reduction in specific areas. The primary areas of change were the Qinghai Plateau and the Qaidam Basin, with significant changes observed in provincial capitals along river valleys, industrial cities in the basins, and tourist cities. (2) In earlier years, construction land mainly transitioned to cropland and grassland, while in later years, it primarily converted to water bodies and water conservancy land. Early expansion mainly occupied unused land, whereas later expansion predominantly encroached on ecological land such as cropland, forest, and grassland. Regional differences in land-use transitions were evident: the Northern Tibet Plateau and Qaidam Basin showed higher proportions of transitions to water bodies, water conservancy land, and unused land, while the expansion mainly occupied grasslands and unused land; in other regions, construction land predominantly shifted between cropland and grassland. (3) The IRSEI values of construction land in the regions of Qinghai-Tibet Plateau were ranked as follows: Sichuan-Tibet alpine canyon region > Qilian Mountains region > Southern Tibet valley region > Qinghai Plateau > Qaidam Basin > Northern Tibet Plateau. (4) Overall, construction land transition demonstrated negative ecological effects. In the Northern Tibet Plateau and Qaidam Basin, the ecological effects resulting from the transfer of unused land and grassland to construction land contributed the most, while in other regions, ecological land was the primary contributor to the ecological effects. [Conclusion] From 2000 to 2020, the transition of construction land on the Qinghai-Tibet Plateau and its resulting ecological and environmental effects exhibited significant regional differences. In the future, differentiated policies and measures can be implemented to promote the sustainable development of Qinghai-Tibet Plateau.